Effect of Vertical Subsurface Wetlands in Removing Chemical Nitrogen and Phosphorus from Secondary Effluent of Wastewater Treatment Plant - Wang, Hao; Li, Xuejin; Zhang, Lei (Asian Journal of Chemistry, 2012)
The secondary effluent of wastewater treatment plants in Tangshan area was used for this study. Two vertical subsurface constructed wetlands were carried out treating it. The chemical pollutant indexes of ammonia nitrogen (NH3-N), total nitrogen (TN) and total phosphorus (TP) were analyzed for evaluating the removal efficiency of pollutants from the secondary effluent of wastewater treatment plant. The vertical zeolite subsurface wetland and vertical modified zeolite subsurface wetland showed different behaviours for nitrogen and phosphorus removals. Meanwhile, vertical modified zeolite subsurface wetland exhibited more remarkable removal effects on NH3-N, total nitrogen and total phosphorus.